Optimising job dispatching at a smart pharmacy - Liaw, Ying Qi (2019)
As Singapore faces an aging population and labour crunch, the shortage of healthcare professionals to cope with the increase in demand for healthcare is a growing concern. To cope with this, hospitals have explored the use of technology to increase the operational efficiencies of hospitals. Through the use of technology, hospitals hoped to diversify the nature of allied healthcare professionals and reduce the waiting time for patients. One such initiative was the Outpatient Pharmacy Automated System in the pharmacies of hospitals. This project focuses on the ways to further increase the efficiencies of an Outpatient Pharmacy Automated System to further reduce waiting time for patients. The problem was further broken down into two parts, Storage Assignment within the automated pharmacy and Routing Policy in dispensing drugs in the prescriptions. This project adapted strategies used by different Automated Storage and Retrieval Systems and drew parallels from Optimisation Theory to develop a unique set of mathematical models and algorithm which was applied onto the Outpatient Pharmacy Automated System. The new set of methodology was tested against the current methodology and conclusions with regards to the methods were made from the results obtained.